Assessing Minipigs as Superior Non-Rodent Pre-Clinical Models: Insights from Plasma Protein Binding and Metabolism of Marketed NSAIDs Compared Across Species - Mondal, Subodh; Uppal, Ritika; CS, Satish (Jordan Journal of Pharmaceutical Sciences, 2025)
As per regulatory authorities’ requirements, pre-clinical studies need to be conducted in at least one rodent and one non-rodent species. Usually, dogs are considered the non-rodent pre-clinical species of choice even though minipigs and monkeys are physiologically closer to humans than dogs. The aim of this study was to demonstrate that minipigs may be a better model for pre-clinical studies compared to dogs for some drug classes. In the present in vitro study, plasma protein binding and metabolic stability in liver microsomes of nine marketed non-steroidal anti-inflammatory drugs (NSAIDs) was evaluated in minipig, dog, monkey, and human species. Eight out of nine tested NSAIDs showed statistically similar plasma protein binding in minipig and human plasma which was different from dog and monkey plasma. Similarly, drug metabolism assays showed similar metabolism in minipig and human liver microsomes, which was different compared to dog and monkey liver microsomes. The results from both the assays showed greater similarity between minipigs and humans suggesting the use of minipig species as a better pre-clinical non-rodent model for NSAIDs instead of the conventional dog species. Additionally, the use of the more accessible minipig species may help in saving time and resources during pre-clinical studies and may help the safety studies in humans during later stage clinical trials.